The development of the Lao animation industry from past to present - Pimpiset, Pitipong (International Journal of Engineering and Technology, 2018)
This paper explores the development of the Lao animation industry from past to present. It specifically focuses on the real development of Lao animation that has never been previously undiscovered. Interestingly, there have been attempts to collect data regarding Lao animation by researchers and journalists in the past. However, due to constraints of language, cultural understanding, and a lack of trust by the Laotian artists, it has been difficult to obtain permission to view their artworks, observe their work environment, and interview them for the more in-depth information that has been typically kept secret from foreigners. This article, as previously mentioned, aims to study the development of Lao animation as it has been gradually developed from simple cartoons to the advanced 3D animation which represents the embracing of digital culture in Lao PDR. Furthermore, in order to consider Lao animation as an industry, systems theory was used in this study, along with other theories, in order to explain context including; globalization, modernization and diffusion theories. These theories will help explain the collected data gathered by the research tools that included; observation, in-depth interview and focus groups. Therefore, according to the systems theory, any industry can be viewed as system when considering four elements; input, process, output and outcome. The results show that the Lao animation industry started to form in the late 1990s, after the Lao government officially announced its "New Economic Mechanism" (NEM) during the second five year period of the national socio-economic development plan (1986-1990). Since then, there have been some interesting factors and elements that continuously appeared to help facilitate the development of the Lao animation industry including; input, process, output and outcome. Nonetheless, a lack of associated documentation and research papers made it impossible to focus on what should be improved. Today, the Lao animation industry is currently struggling with different issues. Consequently, in order to understand the development of the Lao animation industry and its trend towards a creative industry approach, an understanding of the digital culture and an analysis of its related factors is useful and might help provide guidance or recommendations for future development.Â Â Â